Metabolic Syndrome Exacerbates Pulmonary Hypertension due to Left Heart Disease. Issue 4 (2nd August 2019) - Ranchoux, Benoît; Nadeau, Valérie; Bourgeois, Alice; Provencher, Steeve; Tremblay, Éve; Omura, Junichi; Coté, Nancy; Abu-Alhayja'a, Rami; Dumais, Valérie; Nachbar, Renato T.; Tastet, Lionel; Dahou, Abdellaziz; et al.
Abstract : Rationale: : Pulmonary hypertension (PH) due to left heart disease (LHD), or group 2 PH, is the most prevalent form of PH worldwide. PH due to LHD is often associated with metabolic syndrome (MetS). In 12% to 13% of cases, patients with PH due to LHD display vascular remodeling of pulmonary arteries (PAs) associated with poor prognosis. Unfortunately, the underlying mechanisms remain unknown; PH-targeted therapies for this group are nonexistent, and the development of a new preclinical model is crucial. Among the numerous pathways dysregulated in MetS, inflammation plays also a critical role in both PH and vascular remodeling. Objective: : We hypothesized that MetS and inflammation may trigger the development of vascular remodeling in group 2 PH. Methods and Results: : Using supracoronary aortic banding, we induced diastolic dysfunction in rats. Then we induced MetS by a combination of high-fat diet and olanzapine treatment. We used metformin treatment and anti–IL-6 (interleukin-6) antibodies to inhibit the IL-6 pathway. Compared with sham conditions, only supracoronary aortic banding+MetS rats developed precapillary PH, as measured by both echocardiography and right/left heart catheterization. PH in supracoronary aortic banding+MetS was associated with macrophage accumulation and increased IL-6 production in lung. PH was also associated with STAT3 (signal transducer and activator of transcription 3) activation and increased proliferation of PA smooth muscle cells, which contributes to remodeling of distal PA. We reported macrophage accumulation, increased IL-6 levels, and STAT3 activation in the lung of group 2 PH patients. In vitro, IL-6 activates STAT3 and induces human PA smooth muscle cell proliferation. Metformin treatment decreased inflammation, IL-6 levels, STAT3 activation, and human PA smooth muscle cell proliferation. In vivo, in the supracoronary aortic banding+MetS animals, reducing IL-6, either by anti–IL-6 antibody or metformin treatment, reversed pulmonary vascular remodeling and improve PH due to LHD. Conclusions: : We developed a new preclinical model of group 2 PH by combining MetS with LHD. We showed that MetS exacerbates group 2 PH. We provided evidence for the importance of the IL-6–STAT3 pathway in our experimental model of group 2 PH and human patients. Abstract : Supplemental Digital Content is available in the text.